FACING SOIL AND GROUND WATER POLLUTION IN SOUTH TEHRAN (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
In the article an environmental pollution of South Tehran (Rey Industrial area) was studied. The oil pollution of facing soil and ground water in Ray area was actualized since early 1970's. The aim of the study was to carry out a method to solve this problem. It is shown the polluting material is the light oil and is measured the annual movement of polluting oil about 2.6 m per year. In circumstances like these an urgent measures regarding to the related polluted region and pollution source, as well as detailed and preliminary investigations are recommended.
Keywords: South Tehran; Rey Industrial area; oil pollution; facing soil; ground water